2019
DOI: 10.1111/psyp.13363
|View full text |Cite
|
Sign up to set email alerts
|

Positive emotional reactions to loved names

Abstract: Studies concerning personal attachment have successfully used loved familiar faces to prompt positive affective and physiological reactions. Moreover, the processing of emotional words shows similar physiological patterns to those found with affective pictures. The objective of this study was to assess whether the passive viewing of loved names would produce a pattern of subjective and physiological reactivity similar to that produced by the passive viewing of loved faces. The results showed that, compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
(92 reference statements)
2
6
0
Order By: Relevance
“…The present study showed heart rate responses that replicated, for the first time within an fMRI scanner, previous findings concerning loved familiar faces [19], [42], [43] and names [47]: larger increases in heart rate for loved faces and names than for neutral ones. Although not significant, there was also a tendency for the accelerative response to be larger for faces than names.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present study showed heart rate responses that replicated, for the first time within an fMRI scanner, previous findings concerning loved familiar faces [19], [42], [43] and names [47]: larger increases in heart rate for loved faces and names than for neutral ones. Although not significant, there was also a tendency for the accelerative response to be larger for faces than names.…”
Section: Discussionsupporting
confidence: 90%
“…This pattern of response is similar to the heart rate response found in numerous studies using the passive picture-viewing paradigm when participants were viewing highly arousing pleasant pictures selected from the IAPS [7]. It is also similar to the heart rate response found in previous studies when participants were viewing loved faces and names [19], [42], [43], [47]. The major difference with respect to previous studies was in reference to the latency of the accelerative response.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The model thus predicts an increased startle, resulting in lower overall costs, when beneficial opportunities are available such as during reward anticipation. Other exceptions include that startle was potentiated when viewing the names of loved ones compared to neutral or famous names 52 and that anxiolytics had no effects on fear-potentiated startle 53 . Likewise, enrichment 25 and preferred home cage odour 54 did not attenuate startle in rats, and chronic mild stress failed to potentiate startle in mice 55 .…”
mentioning
confidence: 99%